Growth and Secondary Metabolites Production of Centella asiatica (L.) Urb. Cultivated at Different Phosphate Application Rates in Acid Soil - Vinolina, Noverita Sprinse; Sigalingging, Riswanti (Trends in Sciences, 2022)
Centella asiatica (L.) Urb. is a widely known medicinal plant for dermatological and non-dermatological diseases. The demand for C. asiatica extracts continues to increase but its availability is markedly depleted due to exploitation and limited cultivation. This study was conducted to evaluate the phosphate growth responses and variation of secondary metabolites production of C. asiatica cultivated at different phosphate application rates in acid soil in Indonesia. The soil pH used in this study was 2.76. Rates of phosphate application were 0 kg per plant as control plant, 20, 40, 60, 80 and 100 kg ha-1, respectively. Results showed that the plants applied with 40 kg ha-1 phosphate resulted in the highest number of leaves, petiole length, total leaf area, and number of tendrils and stolons which lead to the higher biomass. C. asiatica produced various types of secondary metabolites, i.e asiaticoside, madecassoside, asiatic acid, saponin, tannin, phenolic, flavonoid, triterpenoid, steroid, and glycoside. The production of secondary metabolites was optimized by the application of 20 kg ha-1 phosphate. It can be concluded that the application low dosage of phosphate can enhance the growth and secondary metabolites production of C. asiatica cultivated in acid soil. HIGHLIGHTS Gotu kola is well-known medicinal plant that has which has been used for generations and its benefits has been confrmed by the consumers Gotu kola can grow in both lowlands and highlands but the centellosides contents in gotu kola affected by the growing medium and phosphorus application The demand for simplicia is increasing, while the availability of gotu kola is limited in nature may cause gotu kola become rare and even endangered. Thus, it is necessary to cultivate gotu kola to maintain good quality and quantity The specific target to be achieved is the availability of gotu kola with optimal centelloside content GRAPHICAL ABSTRACT